Pendampingan Asesmen Kebutuhan Belajar Siswa dengan Hambatan Perkembangan Sosial-Emosi dan Perilaku di Sekolah Cordova Fun Islamic Learning: Sebuah Upaya Kolaboratif - Dimas Arif Dewantoro; Rizqi Fajar Pradipta; Hanif, Ellora Fauziyyah; Nanda Viorella (Politeknik Piksi Ganesha Indonesia, 2025)
Students with social-emotional and behavioral developmental barriers tend to require a special educational approach, so the implementation of learning needs assessments is needed. Lack of teacher understanding of assessment is another factor inhibiting optimal inclusive education. assistance in assessing learning needs for students with social-emotional and behavioral developmental barriers in this school, aims to improve the competence of teachers and parents in identifying and responding to students' educational needs. With participatory methods that include lectures, discussions, demonstrations, and workshops. while the evaluation is comprehensive, both process and results, through assessing participant activeness, cooperation, skills, and mastery of the material. the assessment results show that most students are able to understand instructions and complete simple tasks, but there are students who need special interventions related to deviant behavior. it is hoped that through the assessment carried out, teachers and parents provide appropriate and optimal educational services, according to the individual needs of students with special needs which is a step to support their development in an inclusive learning environment.